Retaining structures : design and construction in tropical soils - Kim Huat, Bujang; Han, Khee Kwong; Loh, Wooi Chuan; Ali, Faisal; A. Aziz, Azlan (Universiti Putra Malaysia Press, 2006)
Soil, unlike solid rocks, generally have low strength. It is therefore often not possible to cut or build a high vertical cut and slope in soils without the aid of a retaining structure. Retaining structures are one of those structures that are often built in many civil engineering projects, such as for road cut, basement and flood channel. This book begins with an overview of retaining structures and lateral earth pressure in civil engineering. Detailed discussion on the various earth pressure theories is presented together with a guide on selection of suitable design parameters for retaining structures. Discussion on the design and construction of the various types of retaining structures is provided particularly those relevant to tropical soils. The book also includes a selection guide for suitable retaining structures.